Political communication of Ahok in demolishing slums to normalise River Ciliwung in Jakarta - Nur Kholisoh,; Bylmoreno, Yuventus Newin (Penerbit Universiti Kebangsaan Malaysia, 2020)
The relocation of residents of Kampung Pulo in East Jakarta to make way for the normalisation of River Ciliwung ended in chaos. The chaos was inseparable from the policy of the then governor of the Special Capital Province of Jakarta, Basuki “Ahok” Tjahaja Purnama, known for his harsh and temperamental attitude. This research aims to study the political messages of Governor Ahok in applying a policy to the normalisation of River Ciliwung. The theory of symbolic interaction, the theory of coordinated management of meaning, the theory of conflict, and the theory of speech act are used to analyse the political messages of Governor Ahok and the responses of Kampung Pulo residents to the political messages. This research uses a qualitative approach with a case study method. Research data were collected through in-depth interviews, video recordings and broadcasts of news. This research found inconsistency of the political messages, thus disrupting the implementation of the policy to normalise River Ciliwung. The political messages of Ahok contain euphemism: “our brothers who haven’t had any luck”; metaphor “no rent but maintenance fees”; and labeling “illegal residents”. The residents responded to the political messages in the context of episode, identity, relation and culture. Consequently, both sides were locked in their respective meaning. The residents insisted on demanding compensation for the relocation of the residents as legal ones, while Ahok was confined to the meaning of illegal residents. The dispute culminated in a clash between Kampung Pulo residents and government apparatuses on August 20, 2015.